Persistent Headache and Low Back Pain After Accidental Dural Puncture in the Obstetric Population: A Prospective, Observational, Multicenter Cohort Study. Issue 2 (24th June 2022) - Niraj, G.; Mushambi, M.; Gauthama, P; Patil, A.; Kelkar, A.; Hart, E.; Nurmikko, T.; ,
Abstract : ( Anaesthesia . 2021;76:1068–1076) A documented complication of epidural insertion for labor analgesia is accidental dural puncture (ADP), with an occurrence of 1.2% to 2.6%. Dural puncture and subsequent intracranial hypotension can stimulate the trigeminocervical complex, resulting in postdural puncture headache (PDPH). Although PDPH may cause temporary pain and morbidity, it is commonly accepted that the condition resolves without treatment, as corroborated by the International Headache Society's PDPH definition. However, recent observational studies suggest that ADP may be associated with persistent headache (HA). In addition, limited evidence may suggest that ADP and its treatment with epidural blood patch (EBP) may exacerbate the emergence of postpartum low back pain (LBP). The purpose of this study was to investigate if ADP could be connected to persistent HA and LBP at 18 months postpartum when compared with matched case-control women.